2021
DOI: 10.1093/cvr/cvab264
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors profile of young and older patients with myocardial infarction

Abstract: Myocardial infarction (MI) among young adults (< 45 years) represents a considerable proportion of the total heart attack incidents. The underlying pathophysiologic characteristics, atherosclerotic plaque features and risk factors profile differ between young and older patients with MI. This review article discusses the main differences between the younger and elderly MI patients as well as the different pathogenic mechanisms underlying the development of MI in the younger. Young patients with MI often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 122 publications
(115 reference statements)
3
48
1
5
Order By: Relevance
“…In the past five years, cannabis use has been listed among the risk factors of MI (also associated with an increased risk of cardiovascular mortality) in younger patients [ 52 , 53 ] and at least twelve reviews have appeared drawing attention to adverse cardiac effects of cannabinoids ( Table 1 ). They are based on numerous case reports, epidemiologic or retrospective cohort studies encompassing millions of cannabis users, patients or hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…In the past five years, cannabis use has been listed among the risk factors of MI (also associated with an increased risk of cardiovascular mortality) in younger patients [ 52 , 53 ] and at least twelve reviews have appeared drawing attention to adverse cardiac effects of cannabinoids ( Table 1 ). They are based on numerous case reports, epidemiologic or retrospective cohort studies encompassing millions of cannabis users, patients or hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the electrical remodeling stimulated by the mechanisms described, ROS have also been demonstrated to contribute to atria structural remodeling. Researchers from Slovakia showed that hydroxyl radicals can alter the myofibrillar protein structure and function, promoting myocardial injury and further contributing to the formation of a fertile substrate for the development of arrhythmias [ 5 , 41 ].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…In this article, an update is presented on the emerging data connecting oxidative stress and inflammation to unfavorable atrial structural and electrical remodeling [ 4 ]. Moreover, it is epidemiologically proven that AF is correlated to several factors that either individually or in combination promote the initial development of the arrhythmia and the episodes that characterize the disease [ 5 , 6 ]. Undoubtedly, aging constitutes the primary factor responsible for the pathogenesis of the arrhythmia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myocardial autopsies of COVID-19 patients who suffered heart attacks highlighted the probability of viral myocarditis. SARS-CoV-2 myocarditis has been reported as a significant acute ventricular dysfunction coupled with widespread myocardial edema, while cases of fulminant evolution, complicated with pericarditis, pericardial effusion, and consequent cardiac tamponade have been met [ 10 , 11 ]. In this context, reports of cardiac arrhythmias have been made.…”
Section: Inflammatory Mechanisms In Covid-19-related Cardiovascular D...mentioning
confidence: 99%